A parameter inversion method for coal seam gas pressure based on gas flow rate during drilling process - Shasha Si; Jianhong Kang; Xiu Yang; Ran Zhang; Wei Guo (Fuel, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Mitogenome assembly of the floating-leaved aquatic plant Nymphoides peltata provides insights into organellar evolution and aquatic adaptation in Asterales - Rui Dong; Meng-Na Yu; Lei Zhang; Si-Hao Wang; Xi-Ran Tong; Zhi-Zhong Li (Hydrobiologia, 2026)

H₂O₂-induced green synthesis of EGCG-flavonoid carrier-free nanoparticles:The role of hydroxyl group number governing formation and function - Qian Zhou; Ran Feng; Chen-Chen Wang; Si-Jie Wu; Qiu-Ya Ji; Ran Meng; Bao Zhang (Food Chemistry, 2026)

Ligand-specific tuning of an olfactory receptor to respond to sex pheromones in cowpea weevil, Callosobruchus maculatus - Hao-Ran Lu; Shan Li; Li-Jie Zhang; Kai Shi; Si-Qin Ge; Zhen Zou (Insect Biochemistry and Molecular Biology, 2026)

Polysaccharide-based inflammatory microenvironment-responsive nanocarriers for ulcerative colitis: Advances in design, mechanisms, and therapeutic applications - Si-Jie Wu; Ran Feng; Ran Meng; Qiu-Ya Ji; Han Tao; Bao-Cai Xu; Bao Zhang (Carbohydrate Polymers, 2026)

Structural and textural enhancement of oleogels via l-lysine-mediated whey protein cryogel modification - Run-Hao Fu; Ran Feng; Si-jie Wu; Bao-Cai Xu; Bao Zhang (Food Chemistry, 2026)

Sub-denaturing thermal pretreatment modulates lactoferrin-quercetin interactions: Structural dynamics, binding mechanisms, and functional synergy - Si-Jie Wu; Qi-Bin Kuang; Ran Feng; Ran Meng; Qiu-Ya Ji; Han Tao; Bao-Cai Xu; Bao Zhang (Food Hydrocolloids, 2026)

Insights into the binding mechanism of Monascus pigment with Holo-ovotransferrin by multispectral and molecular dynamics simulation - Yan Fan; Xi-Yuan Guan; Can-Huan Liang; Jia-Lin Chen; Si-Ran Zhang; Sheng Huang; Qin Wang; Wen-Hua Yang (Food Chemistry, 2026)

Sex differences in locomotor recovery across mating contexts in Drosophila melanogaster - Rui Han; Jun Zhang; Xin-Hui Chen; Jing-Wen Duo; Yi-Yi Li; Yi-Ran Chen; Si-Tong Chen; Lin-Xiang Liu; Xiang-Haoran Lin (Behavioural Processes, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Curcumin-mediated photodynamic action disturbs TOM70-depedent MIC60 import to damage mitonchondria against breast cancer - Xiang-Yi Zhao; Min Yan; Liang Zheng; Chang-Long Gou; Qi Huang; Liu-Gen Li; Xin-Ran Yu; Jing-Yu Lu; Cui Hu; Si-Han Zhang; Cunqing Kong; Fan Leng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Synergistic dual mechanisms in emulsion stabilization: hierarchical reinforcement via 3D oleogel networks and nanoparticle-engineered interfacial monolayers - Xia-Lian Cui; Bao-Qiu Yang; Ran Feng; Si-Jie Wu; Han Tao; Bao Zhang (Food Research International, 2025)

Exploring the regulation mechanism of digestibility of starch-polyphenol-protein ternary system by pH from multiple perspectives - Ran Meng; Ran Feng; Si-Jie Wu; Qiu-Ya Ji; Han Tao; Bao Zhang (Food Chemistry, 2025)

Rapid and sensitive on-site detection of peach (Prunus persica) species in fruit juices using a RAA-CRISPR/Cas12a approach - Lin Wang; Ran-Ran Xing; Xiao-Ke Liang; Yao-Xian Yu; Qiu-Ju Yi; Si-Yuan Lu; Ting-Ting Deng; Jiu-Kai Zhang; Xu Wang; Ying Chen (Food Control, 2025)

Nanogel cage based on oxidized sodium alginate sacrificial template: Enhanced stability and protein crosslinking performance of immobilized TGase - Si-Jie Wu; Ran Feng; Ran Meng; Qiu-Ya Ji; Han Tao; Bao Zhang (Carbohydrate Polymers, 2025)

Construction of OSA-starch and caffeic acid composite system driven by high pressure homogenization: Multiscale structural evolution and digestibility regulation mechanism - Ran-Ran Deng; Ran Feng; Ran Meng; Si-Jie Wu; Han Tao; Bao Zhang (Food Chemistry, 2025)

New insights into the regulation mechanism of starch digestibility by polyphenol structures in starch-polyphenol-protein ternary system - Ran Meng; Ran Feng; Si-Jie Wu; Qiu-Ya Ji; Han Tao; Bao Zhang (Food Chemistry, 2025)

Mechanism of reducing rice starch digestibility by quinoa protein amyloid-like fibrils pretreated with magnetic field - Ran Meng; Chang-Qing Hong; Ran Feng; Si-Jie Wu; Qiu-Ya Ji; Bao Zhang (Food Chemistry, 2025)

Whey protein-constructed oleogels as cheese fat replacers: Modulating cheese functional behavior via protein structure modification - Si-Jie Wu; Ran Feng; Zi-Yue Chen; Yu-Nong Chen; Bao Zhang (Food Chemistry, 2025)

Chemotaxis-driven Stenotrophomonas pavanii surface-aggregated FastPETase system for in situ degradation of PET microplastics - Si-Qi Chen; Qing-Song Huang; Yang Li; Hao-Ran Zhang; Yan Huang; Jing Wu; Sheng Chen; Zheng-Fei Yan (Chemical Engineering Journal, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

High-precision age constraint for the Xiyingzi Bed of the Jiufotang Formation in western Liaoning, Northeast China - Li-Jun Zhang; Si-Yu Song; Shu-An Ji; Su-Chin Chang; Jahandar Ramezani; Fei Gao; Bo Wang; Hai-Chun Zhang; Da-Ran Zheng (Palaeoworld, 2025)

Effect of cadmium-resistant Proteus mirabilis Ch8 on active ingredients and cadmium content of traditional Chinese medicine Ligusticum sinense cv. Chuanxiong - Ting Li; Lin Liu; Xiu-wen Bao; Fei-fei Liu; Xuan Zhang; Hao-ran Song; Si-jing Liu; Jing Bai; Qing-he Wang; Fei-lin Yang; Yang Li; Shu-qi Niu; et al. (Plant and Soil, 2025)

Two new acorane-type sesquiterpenoids from an endophytic Trichoderma harzianum associated with Paeonia lactiflora Pall - Yun-Peng Sun; Man-Li Zhang; Yang Yu; Ran Sun; Si-Rui Wang; Jin-Song Liu; Guo-Kai Wang (Natural Product Research, 2025)

Dissolved organic matter mitigates the toxicity of silver nanoparticles to freshwater algae: Effects on oxidative stress and membrane function - Jilai Zhang; Chenglei Hu; Ming Jiang; Qianqian Xiang; Sheng Wang; Youbo Su; Naiming Zhang; Zhihao Si; Yuning Mu; Ran Yang (Environmental Pollution, 2025)

Competitive adsorption characteristics of CH4/O2 on coal surfaces: Insights at the molecular scale - Chengyang Peng; Shujing He; Jianhong Kang; Ran Zhang; Shasha Si; Yiqian Zhou (Fuel, 2025)

A UDP-glucuronosyltransferase gene UGT379A1 involved in detoxification of lufenuron in Diaphorina citri - Ze-Hao Huang; Qi Pan; Zhen Wu; Yu-Chao Shen; Si-Chen Li; Qi-Qi Yang; Shao-Hui Zhang; Shuang Lei; Yang-Yang Cui; Li-Li Ding; Shi-Jiang Yu; Liu Liu; et al. (Pesticide Biochemistry and Physiology, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Exploring the binding mechanism and functional properties of lactoferrin-berberine complex: Based on multispectral analysis, molecular docking, and dynamics simulations - Si-Jie Wu; Ran Feng; Ran Meng; Qiu-Ya Ji; Han Tao; Bao-Cai Xu; Bao Zhang (Food Chemistry, 2025)

New insights into rice starch-gallic acid-whey protein isolate interactions: Effects of multiscale structural evolution and enzyme activity on starch digestibility - Ran Meng; Ran Feng; Si-Jie Wu; Qiu-Ya Ji; Han Tao; Bao-Cai Xu; Bao Zhang (Carbohydrate Polymers, 2025)

Strategies, techniques and applications for food authentication based on carbohydrates: A review - Li-feng Li; Xi Shi; Si-min Qi; Xue-ting Zhang; Hau-Yee Fung; Qian-ran Li; Quan-bin Han (Carbohydrate Polymers, 2024)

Loss of CHCHD2 Stability Coordinates with C1QBP/CHCHD2/CHCHD10 Complex Impairment to Mediate PD-Linked Mitochondrial Dysfunction - Yan-Lin Ren; Zheng Jiang; Jia-Yi Wang; Qin He; Si-Xu Li; Xiao-Jing Gu; Yang-Ran Qi; Min Zhang; Wen-Jie Yang; Bei Cao; Jing-Yu Li; Yi Wang; et al. (Molecular Neurobiology, 2024)

Jianpi Huayu Prescription Prevents Atherosclerosis by Improving Inflammation and Reshaping the Intestinal Microbiota in ApoE−/− Mice - Hao-Ran Zhao; Qin-Chi Xian; Xuan-Ming Zhang; Xiao-Yu Ma; Fu-Qiao Wang; Rui-Si Wang; Zhi-Jie Liu; Zhi-Gang Zhang (Cell Biochemistry and Biophysics, 2024)
This study established an LPS-induced RAW264.7 macrophage inflammatory injury model and an AS mouse vulnerable plaque model to observe the effect of JPHYP on macrophage inflammation, plaque formation, blood lipids, inflammation levels, intestinal flora and the influence of TLR4/MyD88/MAPK pathway, and explore the anti-AS effect and molecular mechanism of JPHYP, and detected 16S rRNA of mice intestinal microbes. The difference of intestinal flora in different groups of mice was compared to further explore the intervention effect of JPHYP and clarify the molecular biological mechanism of JPHYP in preventing and treating AS by regulating TLR4/MyD88/MAPK inflammatory signaling pathway and improving intestinal flora.

Immobilization of Nickel- and Cobalt-Based Complexes in NH2-UiO-66 for Efficient CO2 Photoreduction - Yu Jiang; Si-Chao Liu; Li-Ping Zhang; Guo-Wei Guan; Yi-Tao Li; Shuang Ni; Run-Yuan Jiang; Su-Tao Zheng; Hao-Ran Liu; Hao-Ling Lan; Qing-Yuan Yang (Chemical Engineering Journal, 2024)

Cenozoic Indo-Pacific warm pool controlled by both atmospheric CO2 and paleogeography - Ran Zhang; Zhonghui Liu; Dabang Jiang; Yongqiang Yu; Zhongshi Zhang; Yibo Yang; Ning Tan; Dong Si; Qiang Zhang; Xin Zhou (Science Bulletin, 2024)

Sleep microenvironment improvement for the acute plateau entry population through a novel nasal oxygen supply system - Haimeng Li; Ying Zhang; Changqing Yang; Ran Gao; Feng Ding; Thomas Olofsson; Hongxia Zhou; Pengfei Si; Lijun Shi; Angui Li (Building and Environment, 2024)

Erosional modulation of the balance between alkalinity and acid generation from rock weathering - Sen Xu; Aaron Bufe; Si-Liang Li; Erica D. Erlanger; Lishan Ran; Jun Zhong; Ci-Jian Yang; Liwei Zhang; Tingting Ma; Dirk Sachse (Geochimica et Cosmochimica Acta, 2024)

Greening the concrete jungle: Unveiling the co-mitigation of greenspace configuration on PM2.5 and land surface temperature with explanatory machine learning - Yan Li; Yecheng Zhang; Qilin Wu; Ran Xue; Xiaoran Wang; Menglin Si; Yuyang Zhang (Urban Forestry & Urban Greening, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Three-dimensional macroporous structure and surface carbon-coating modification of stainless-steel anode boost bioelectrocatalytic performance - Cheng-Yan Liu; Hao-Yi Cheng; Si-Yuan Zhai; Ran Zeng; De-Xin Zhang; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Effects of iron on the growth, chlorophyll a, total lipids, and fatty acids of Chaetoceros lorenzianus - Zuhao Zhang; Ruibing Peng; Xinyi Xia; Pingping Liu; Si Chen; Ran Xia; Xiamin Jiang; Maowang Jiang; Jianyuan Lin (Journal of Applied Phycology, 2023)

Ecological adaptation shaped the genetic structure of homoploid ferns against strong dispersal capacity - Si‐Qi Liang; Xian‐Chun Zhang; Ran Wei (Molecular Ecology, 2022)
The formation of spatial genetic structure with the presence of extensive gene flow, an evolutionary force which is generally expected to eliminate population‐specific variation and maintain genetic homogeneity, remains poorly understood. Homosporous ferns, which spread by spores through wind and possess long distance dispersal capacity, provide an ideal system to investigate such a process. Here, using a homoploid fern lineage, the Athyrium sinense complex, we used reduced‐representation genomic data to examine spatial genetic structure and explored potential driving forces including geographical distance, environment, climatic history and external dispersal constraints. Our findings showed a clear north‐south divergence at the genetic, morphological and ecological levels between both sides of 35°N in East Asia. Fluctuant and heterogeneous climatic condition was demonstrated to play a crucial role during the formation of the divergence. Our results suggested that this lineage was able to migrate southward and colonize new habitat as a result of the Quaternary climatic fluctuation. Furthermore, the present genetic structure is attributed to adaptation to heterogeneous environments, especially temperature difference. In addition to ecological adaptation, we found clues showing that canopy density, wind direction as well as habitat continuity were all likely to constrain the effect of gene flow. These results demonstrated a diversification process without ploidy changes in ferns providing new insights for our present knowledge on ferns’ spatio‐temporal evolutionary pattern. In particular, our study highlights the influence of environmental heterogeneity in driving genetic divergence against strong dispersal capacity.

Dysregulation within the salience network and default mode network in hyperthyroid patients: a follow-up resting-state functional MRI study - Bo Liu; Li Wen; Qian Ran; Si Zhang; Junhao Hu; Mingfu Gong; Dong Zhang (Brain Imaging and Behavior, 2020)

Enzymatic removal of paracetamol from aqueous phase: horseradish peroxidase immobilized on nanofibrous membranes - Ran Xu; Yifang Si; Fengting Li; Bingru Zhang (Environmental Science and Pollution Research, 2015)

Estimation of quality factors by energy ratio method - Zong-Jun Wang; Si-Yuan Cao; Hao-Ran Zhang; Ying-Ming Qu; Dian Yuan; Jin-Hao Yang; Guan-Ming Shao (Applied Geophysics, 2015)

Selenium Deficiency Inhibits the Conversion of Thyroidal Thyroxine (T4) to Triiodothyronine (T3) in Chicken Thyroids - Shi-lei Lin; Cong-wu Wang; Si-ran Tan; Yang Liang; Hai-dong Yao; Zi-wei Zhang; Shi-wen Xu (Biological Trace Element Research, 2014)

Possible Correlation of Selenoprotein W with Inflammation Factors in Chicken Skeletal Muscles - Qiong Wu; Hai-Dong Yao; Si-ran Tan; Zi-Wei Zhang; Yao-hong Zhu; Shiwen Xu (Biological Trace Element Research, 2014)

Analysis of quality factors for Rayleigh channel waves - Xiao-Hui Yang; Si-Yuan Cao; De-Chun Li; Peng-Fei Yu; Hao-Ran Zhang (Applied Geophysics, 2014)

The genetic mechanism of a translational landslide - Xuan-Mei Fan; Qiang Xu; Zhuo-Yuan Zhang; Dong-si Meng; Ran Tang (Bulletin of Engineering Geology and the Environment, 2009)